Measurement of the intensity ratio of Auger and conversion electrons for the electron capture decay of 125I. (21st March 2018) - Alotiby, M; Greguric, I; Kibédi, T; Lee, B Q; Roberts, M; Stuchbery, A E; Tee, Pi; Tornyi, T; Vos, M
Abstract: Auger electrons emitted after nuclear decay have potential application in targeted cancer therapy. For this purpose it is important to know the Auger electron yield per nuclear decay. In this work we describe a measurement of the ratio of the number of conversion electrons (emitted as part of the nuclear decay process) to the number of Auger electrons (emitted as part of the atomic relaxation process after the nuclear decay) for the case of 125 I. Results are compared with Monte-Carlo type simulations of the relaxation cascade using the BrIccEmis code. Our results indicate that for 125 I the calculations based on rates from the Evaluated Atomic Data Library underestimate the K Auger yields by 20%.